THE ROLE OF PRODUCTIVE ZAKAT IN REDUCING THE INCOME DISCREPANCY IN SOUTH KALIMANTAN PROVINCE - Yusuf Asyahri; Faqih El Wafa (IAIN Manado, 2022)
This article aims to analyze the distribution of zakat funds, the impact of zakat funds on income, and the distribution of zakat in reducing income inequality in South Kalimantan Province. The analytical method used is the sample Paired t-test and the Lorenz Curve and Gini Ratio, with a mixed method. The results of the study provide findings, First, the distribution of zakat funds to Mustahik has gone through the stages of indicators including Goal Setting; Planning; Organizing; Staff Filling; Briefing; Supervision; Control; and Coordination. Second, distinguishing income before and after the existence of productive zakat assistance for economic empowerment. Third, the Gini coefficient shows that income inequality can be reduced by a reduction index of 0.1493 after the existence of productive zakat. Thus, it can be concluded that there is a difference in income before and after the distribution of productive zakat for economic empowerment and income inequality can be reduced by a reduction index of 0.1493 after the existence of zakat.